Embracing Digital Technology (MIT Sloan Management Review, 2013)
A study by MIT Sloan Management Review and Capgemini Consulting finds that companies now face a digital imperative: adopt new technologies effectively or face competitive obsolescence. While there is consensus on the importance of adopting digital technology, most employees find the process complex and slow. Many say their leaders lack urgency and fail to share a vision for how technology can change the business. Companies that succeed tend to have leaders who share their vision and define a road map, create cross-organizational authority for adoption and reward employees for working towards it.